2016
DOI: 10.5897/ajar2016.10852
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses of sunflower grown under levels of water replacement and potassium fertilization

Abstract: Water deficit is one of the limiting factors of agricultural production, especially in semi-arid regions. In this sense, the aim of this study was to evaluate the growth and the physiological characteristics of sunflower cv. Hélio 251 at different levels of water replacement and potassium doses in an experiment conducted in the greenhouse of the Center for Technology and Natural Resources of UFCG, Campina Grande, PB. The experiment was laid out in randomized complete block design, by studying five levels of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…(7) Potassium application contributes plants to approach longer root length as well through the condition of drought stress. The positive response of sunflower productivity to potassium application was described by several investigators (Ahmad et al, 2011;Chajjro et al, 2013;Ahmad et al, 2014;Hakan and Zengin, 2014;Jan and Hadi, 2015;Guilherme et al, 2016 andSabrina et al, 2016).…”
Section: Potassiummentioning
confidence: 69%
“…(7) Potassium application contributes plants to approach longer root length as well through the condition of drought stress. The positive response of sunflower productivity to potassium application was described by several investigators (Ahmad et al, 2011;Chajjro et al, 2013;Ahmad et al, 2014;Hakan and Zengin, 2014;Jan and Hadi, 2015;Guilherme et al, 2016 andSabrina et al, 2016).…”
Section: Potassiummentioning
confidence: 69%
“…[30] used sunflower hybrids (SF-187 and Parsun-1) against various K levels and found varied response of sunflower hybrids to increased K levels, However, a combination of 150:100:100 kg ha -1 NPK resulted in optimistic results regarding agronomic performance and plant nutrient uptakes. [32] evaluated the impact of potassium use efficiency of sunflower hybrids and found that Helio 251 had higher potassium use efficiency as compared to rest of the hybrids.…”
mentioning
confidence: 99%